BRAND IMAGE, STAFF INTERACTION BEHAVIOR AND OVERALL SERVICE QUALITY ON DECLINING SALES: A CASE STUDY OF STARBUCKS COFFEE MALAYSIA - Chee, Zhu Yang; Mak, Seen Theng; Roy, Sharwin; Ma, Junzhe; Ali Akbar, Rafatnia (INTI International University, 2023)
The selected company for the case analysis and evaluation is Starbucks Coffee Malaysia Company. The company is selected due to its strong presence and established reputation in the food and beverages market, as well as its effective business approach. The corporate profile will consist of four subparts: the company's history, functions, brand positioning and competitive strategies of the organization within the local context of Malaysia. This study aims to investigate the variables contributing to the decline in sales at Starbucks Malaysia. This study examines three independent variables that are associated with the causes contributing to the decline in sales: brand image, staff interaction behavior, and overall service quality, also referred to as customer service. We shall conduct a comprehensive analysis of how these three factors contributed to the decline in Starbucks' sales in Malaysia. The study was done by distributing the questionnaire via Google Form to a sample of 120 Starbucks customers in Malaysia. The dependent variable has a positive correlation with all of the independent factors. The study's consequences lie in its ability to offer insights into the variables that contributed to the decline in sales, as well as strategies to address these issues and enhance sales while minimizing the risk of further declines.